Delineation of groundwater aquifers using VES and 2D imaging techniques in north Badra area, Eastern Iraq - Thabit, Jassim; Thabit, Jassim; AL-Hameedawie, Mohammed (Iraqi Journal of Science, 2023)
The resistivity survey was carried out by using vertical electrical sounding (VES) and 2D imaging techniques in the northern Badra area, Eastern Iraq. Eleven VES points distributed on two parallel profiles and six 2D imaging stations were applied using long survey lines.In general, two types of aquifers are recognized in the study area. The first is the Quaternary aquifer, which appears in all geological sections and inverse model of 2D imaging stations (2DS).This aquifer can be divided into upper and lower aquifers as shown in (2DS1), (2DS3), and (2DS4). Generally, the thickness of this aquifer ranges between (30-200 m) which occurs at a depth of (10-30m) according to geological sections, while its thickness ranges between (35-180m) and occurs at depth (10-45m) according to the inverse model of 2D imaging stations. The second is the AL-Mukdadiya aquifer, which appears only in 2DS1 at a depth of (140m), and it thickness is more than (80m).The comparison between VES and 2D imaging techniques revealed that the VES technique is the best in delineating the boundaries between layers. However, the 2D imaging technique is better at delineating the aquifers, and at determining the vertical and horizontal changes in resistivity within layers and aquifers, and it also succeeded in recognizing the upper and lower aquifers of quaternary aquifer as shown in (2DS1), (2DS3), and (2DS4). Therefore, 2D imaging is better at recognizing more layers or aquifers than that of VES technique, especially with the gradual decrease (or increase) in resistivity values or layers with small thickness. Also, the VES technique showed a high depth of investigation (DOI) in comparison with 2D imaging technique.